BSA-seq Identifies a Major Locus on Chromosome 6 for Root-Knot Nematode (Meloidogyne graminicola) Resistance From Oryza glaberrima - Kaur, Gurwinder; Yadav, Inderjit Singh; Bhatia, Dharminder; Vikal, Yogesh; Neelam, Kumari; Dhillon, Narpinderjeet Kaur; Praba, Umesh Preethi; Mangat, Gurjit Singh; Singh, Kuldeep (Frontiers in Genetics, 2022)
Root-knot nematode (Meloidogyne graminicola) is one of the emerging threats to rice production worldwide that causes substantial yield reductions. There is a progressive shift of the cropping system from traditional transplanting to direct-seeded water-saving rice production that favored the development of M. graminicola. Scouting and deploying the new resistance genes is an economical approach to managing the root-knot nematodes. Here, we report the inheritance of root-knot nematode resistance in Oryza glaberrima acc. IRGC102206 is governed by a single dominant gene. Traditional mapping coupled with BSA-seq was used to map nematode resistance gene (s) using the BC1F1 population derived from a cross of O. sativa cv. PR121 (S) and O. glaberrima acc. IRGC102206 (R). One major novel genomic region spanning a 3.0 Mb interval on chromosome 6; and two minor QTLs on chromosomes 2 and 4 were the potential genomic regions associated with rice root-knot nematode resistance. Within the QTL regions, nineteen putative candidate genes contain eighty-one non-synonymous variants. The detected major candidate region could be fine mapped to accelerate marker-assisted breeding for root-knot nematode resistance in rice.